Effect of a high-fat diet and leptin on STAT3 phosphorylation in hippocampal astrocytes. Issue 1 (7th December 2022) - Naranjo, V.; Merino, Beatriz; Del Olmo, N.; Frago, L.M.; Chowen, J.A.; Ruiz-Gayo, M.; Cano González, Victoria
Abstract : Diet-induced obesity evoked by high-fat diets (HFD) impairs hippocampus-dependent learning and memory in juvenile mice. Leptin resistance has been proposed to play a role in this phenomenon. We have recently reported that leptin receptor (LepR) knockdown in astrocytes yields mice displaying both impaired synaptic plasticity and low Glu uptake efficacy in the hippocampus. These findings support the pivotal role for astrocyte LepR in hippocampus function, which could eventually be affected by HFD consumption. Objective: The aim of the current study was to evaluate the influence of HFD on the functionality of LepR by quantifying phosphorylated levels of 705 Tyr-STAT3 in hippocampus astrocytes from mice that consumed an HFD either during the juvenile or the adult period. Methods: Five- and eight-week-old male mice, fed during 8 weeks with either control chow or HFD, received a single dose of leptin and their brains were prepared for immunofluorescence to identify double-positive GFAP/p 705 Tyr-STAT3 cells. Results: HFD intake led to increased pSTAT3 immunoreactivity in GFAP + cells in the CA1/CA3 hippocampus areas. The effect was observed both in adolescent and adult mice. Leptin increased pSTAT3 immunoreactivity in control animals but was devoid of effect in HFD mice. HFD itself has no effect on the number of GFAP + cells. Conclusions: Our data show that regular intake of HFD enhances STAT3 signaling in CA1/CA3 astrocytes, an effect that could be linked to the increase of leptin triggered by HFD. The increase of pSTAT3 might be integral to homeostatic mechanisms aimed at maintaining hippocampus function.